Fractional singular differential systems of Lane-Emden type : existence and uniqueness of solutions - Gouari, Yazid (2021)
A coupled system of singular fractional differential equations involving Riemann–Liouville integral and Caputo derivative is considered in this paper. The question of existence and uniqueness of solutions is studied using Banach contraction principle. Furthermore, the question of existence of at least one solution is discussed. At the end, an illustrative example is given in details.